Effect of Rice Mill Wastes Application on Selected Soil Physical Properties and Maize Yield (Zea mays l.) On an Ultisol in Abakaliki Southeastern Nigeria - C, Njoku; C.N., Mbah; C. I., Okonkwo (Global Journal of Food and Agribusiness Management, 2012)
An experiment was carried out in 2008, 2009 and 2010 (residual) cropping season at Teaching and Research Farm of Faculty of Agriculture and Natural Resources Management, Ebonyi State University, Abakaliki to determine the long term effect of burnt and unburnt rice mill wastes application on soil physical properties and maize yield. The experiment was laid out in Randomized Complete Block Design (RCBD) with three replicates. Seven treatments were included in the study: burnt rice mill waste at 10 and 20 t ha-1 (BW10) and (BW20), unburnt rice mill waste at 10 and 20 t ha-1 (UW10) and (UW20), mixture of burnt + unburnt rice mill waste (1:1) at 10 and 20 t ha-1 (BUW10) and (BUW20), and a control (C). The results showed that rice mill wastes significantly (P < 0.05) improved soil physical properties (hydraulic conductivity and aggregate stability) and maize yield, compared to control across the three cropping seasons. The order of increase in crop grain yield in 2008 and 2009 cropping seasons were BW20>BUW20> BUW10>UW20>BW10>UW10>C and BUW20>BUW10>BW20> UW20>BW10>UW10>C. Control recorded the lowest value of crop grain yield (0.12 t ha-1 ) in 2010 cropping season. At rate of 20 t ha-1 BW, BUW and UW recorded highest maize grain yield of 4.18, 4.06 and 1.70 t ha-1 in 2008, 2009 and 2010 cropping seasons, respectively. Therefore, rice mill wastes at these rates studied (10 and 20 t ha-1 ) could be used as soil amendment since it improved soil physical properties and increased maize yield